An Integrative Approach to Needs Assessment and Curriculum Development of the First Public Health Major in Singapore - Lim, Raymond Boon Tar; Teng, Cecilia Woon Chien; Azfar, Julian; Bun, Diane; Goh, Gina Junna; Lee, Jeannette Jen-Mai (Frontiers in Public Health, 2020)
Although public health undergraduate education is increasingly popular in the West, studies describing the needs assessment and curriculum development of public health undergraduate education programs are lacking in the Asia Pacific. The objective of this study was to describe the needs assessment and curriculum development of a second major in public health for undergraduates in the National University of Singapore, the first in Singapore. We used the integrated framework for curriculum development in higher education which consisted of five stages. In Stage 1, the environment was assessed on the need for a new curriculum. Externally, there was a demand for public health workforce in Singapore based on a review of reports from the Ministry of Health and the job portals. Internally, there was a demand from existing students of the University, along with support from the faculty to offer a new curriculum. There was no university in Singapore offering an undergraduate major program in public health. In Stage 2, competencies to be developed were identified from public health job descriptions using job portals, the needs of public health stakeholders, and competencies listed in the public health curriculum accreditation frameworks such as the Council on Education for Public Health. In Stage 3, based on data triangulation, the curriculum was designed as a second major that is offered to all students of the university from year 2 onwards. Students have to complete a total of 12 modules, of which six are core and six are elective. The capstone module is a 320-hour internship module where students will be attached to public health related agencies, organizations or non-governmental organizations. Our curriculum is generally aligned with undergraduate public health programs in other established universities in the United States of America, United Kingdom, Australia and Hong Kong. In Stage 4, various pedagogical strategies were identified for the core modules. We are currently at Stage 5 where implementation, monitoring and evaluation are still being carried out. We hope that the lessons learnt will serve to inform other universities in the Asia Pacific which are considering implementing such programs and broadening their offerings in public health education.